Desakan Penanganan Peristiwa, Penangkapan, Penahanan, dan Penyiksaan Anak di Bawah Umur oleh Anggota Polsek Widang Tuban: Perspektif Etika Profesi Hukum dan Alternatif Penyelesaian Sengketa - Silva Fransisca Utami; Mega Dewi Ambarwati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The arrest, detention and abuse of minors carried out by members of the Widang Police in Tuban, East Java is a serious violation of children's human rights and the values of justice. In law enforcement in Indonesia, children enjoy special normative protection through law and international human rights instruments such as the Convention on the Rights of the Child which has been ratified by Indonesia. However, in practice, violations of children's rights still often occur, especially in cases of arrest and detention. This case not only reflects deviations from criminal law and child protection standards, but also questions the ethics of the legal profession when handling cases involving children as legal subjects. Arrest and detention of minors should be carried out with a more humane approach, taking into account the child's psychological and developmental conditions, in accordance with the Child Protection Law and other related regulations. In this case, violations of children's rights during arrest and detention by law enforcement officers can damage the integrity of legal institutions and cause long-term trauma for child victims. Physical and mental torture in this process clearly violates established legal principles and is not in line with the moral obligations of law enforcement officers as regulated in legal professional ethics. Legal ethics requires all legal officers to act in accordance with the principles of justice, non-discrimination and respect for human dignity, especially vulnerable children. This research discusses the important role of legal ethics in handling cases of arrest and detention of children. As part of their professional responsibilities, law enforcement officials have a duty to uphold the principles of justice and protect children's rights. However, resolving disputes through formal justice channels often has a negative impact on children, so it is important to consider alternative dispute resolution, such as a victim-centred approach. Restorative justice focuses on healing relationships, repairing the harm experienced by victims, and educating perpetrators to understand their mistakes, without destroying the future of affected children. The restorative justice approach not only focuses on justice for the victim, but also provides the perpetrator with the opportunity to rehabilitate and prevent similar behavior from recurring in the future. In this case, the application of restorative justice can be an effective alternative dispute resolution because it involves all affected parties: minor victims, perpetrators, and the community in the recovery process.